Alpha2‐antiplasmin regulates the development of dermal fibrosis in mice by prostaglandin F2α synthesis through adipose triglyceride lipase/calcium‐independent phospholipase A2. Issue 2 (28th January 2013) - Kanno, Yosuke; Kawashita, Eri; Kokado, Akiko; Okada, Kiyotaka; Ueshima, Shigeru; Matsuo, Osamu; Matsuno, Hiroyuki
Abstract Objective Systemic sclerosis (SSc) is characterized by fibrosis of the skin and visceral organs. Patients with SSc have enhanced plasma levels of the plasmin–α2‐antiplasmin (α2AP) complex, and we recently implicated α2AP in the development of fibrosis through transforming growth factor β (TGFβ) production. This study was undertaken to clarify how α2AP induces TGFβ production and the development of fibrosis. Methods To clarify the detailed mechanism by which α2AP induces TGFβ production, we focused on adipose triglyceride lipase (ATGL)/calcium‐independent phospholipase A2 (iPLA2) and examined whether ATGL/ iPLA2 is associated with α2AP‐induced TGFβ production. The mouse model of bleomycin‐induced SSc was used to evaluate the role of α2AP in the development of fibrosis. Dermal thickness and collagen content were determined in mouse skin treated with phosphate buffered saline or bleomycin. Moreover, we cultured SSc‐like fibroblasts from the bleomycin‐treated mouse skin and examined the production of TGFβ and prostaglandin F2α (PGF2α). Results We found that α2AP binding to ATGL promoted PGF2α synthesis through iPLA2 in fibroblasts, and the PGF2α synthesis that was promoted by α2AP induced TGFβ production in fibroblasts. In addition, the neutralization of α2AP attenuated the production of TGFβ and PGF2α in SSc‐like fibroblasts from mice. The α2AP deficiency attenuated bleomycin‐induced fibrosis and PGF2α synthesis, while the administration of PGF2α to α2AP‐deficient mice facilitated α2AP deficiency–attenuated fibrosis. Conclusion These findings suggest that α2AP regulates the development of fibrosis by PGF2α synthesis through ATGL/iPLA2. The inhibition of α2AP‐initiated pathways might provide a novel therapeutic approach to fibrotic diseases.